Hemodynamic ultrasound evaluation of the mammary gland of buffaloes at different categories - A. Dantas; V.M. Codognoto; V.M.V. Machado; M.G.S. Charlier; R.A. Oliveira; A.M. Jorge; E. Oba (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT The study aimed to evaluate the mammary artery of Murrah crossbred buffaloes at different physiological stages using ultrasonography. Twenty-four pasture-raised animals were divided into four groups (n= 6): heifer calves, yearlings, pregnant animals, and lactating animals. Doppler examinations of the cranial and caudal mammary arteries were performed every 28 days to measure the internal diameter (ID), resistivity index (RI), and pulsatility index (PI). Over one year for heifer calves and yearlings, RI and PI decreased, while ID increased (P<0.0001). No significant differences were found between the cranial and caudal arteries. In pregnant animals, the caudal mammary artery showed lower RI and higher ID during the last five and seven months (P<0.0001), respectively, while lactating animals had higher ID in the first seven months (P<0.0001). These findings suggest the plasticity of the mammary artery during the stages of growth, pre-puberty, pregnancy, and lactation.